Progression towards Online Tar Detection Systems. (December 2017) - Capper, Sean; Khan, Zakir; Kamble, Prashant; Sharp, James; Watson, Ian
Abstract: The most prohibitive aspect with the commercialisation of biomass gasification technology is tar fouling of the product gas. The presence of tar impacts the efficiency of gasification systems and compromises gas quality, rendering it less useful for some downstream applications sensitive to gas quality. Various tar detection methods are reported in the literature which can be differentiated into offline and online techniques. However, offline techniques are found to be time consuming, expansive and require sufficient instrumentation and knowledge to achieve reliable results. Recent advances in online tar detection based on spectral information of individual tar component have attracted much research attention. Among these, fluorescence spectroscopy is a highly promising technique for the provision of distinctive, non-invasive and real time data collection for tar levels which can be easily installed on gasification product gas streams. This paper presents the initial work on developing a low cost tar detection system based on LED induced fluorescence. The detection system mainly consists of a photomultiplier tube (PMT), LED (emission wavelength of 280 nm) and 300 nm longpass colour glass filter. Initial experiments have been carried out with different concentrations (0 to 100 wt%) of phenol (used as a model tar compound) and bio-oil samples from an in-house, downdraft (throated) fixed bed gasification system. The results show a linear increase of fluorescence with phenol and the gasifier bio-oil at different concentrations.